Fiscal Adjustment in Latin America and the Caribbean : Short-Run Pain, Long-Run Gain? - Vegh, Carlos A.; Vuletin, Guillermo; Riera-Crichton, Daniel; Friedheim, Diego; Morano, Luis; Camarena, José Andrée (Washington, DC: World Bank, 2018)
After a growth slowdown that lasted six years, the Latin America and the Caribbean (LAC) region has finally turned the corner and resumed growth at a modest rate of 1.1 percent in 2017 and 1.8 percent expected in 2018. This reflects a more favorable external environment, particularly a recovery in commodity prices. In spite of the benign external environment, most LAC countries still face a fragile fiscal situation. While gradual fiscal adjustments have started in several countries, most countries are still running fiscal deficits and debt levels are high. Further fiscal consolidation is needed to preserve the substantial gains achieved by the region in recent times, in terms of lower inflation, less poverty and inequality, and inclusive growth. This Semiannual Report analyzes the complex decisions regarding fiscal adjustment policies.